(untitled) (Brazilian Journal of Radiation Sciences, 2019)
Currently, among the diseases most feared by women, breast cancer ranks first in the world with an incidence of more than 1.6 million cases and a mortality of more than 521.9 thousand cases by year, which makes this disease the type of cancer with higher incidence and mortality compared to the other types of cancer that mainly affect the female gender, without considering non-melanoma skin cancer. In Brazil, more than 14.4 thousand deaths were registered in 2013 and more than 57 thousand new cases were estimated for 2016. The use of computerized radiography (CR) for the generation of mammographic digital images is widely used in Brazil for the screening of breast cancer. The aim of this investigation is to study the variation of CR plate response to exposure to X-ray beams in a mammography unit. Two CR plates from different manufacturers and a compressed breast phantom containing calcium carbonate structures of different sizes simulating calcifications were used for this study. An X-ray beam generated by 30 kV was selected to realize successive exposures of each plate by performing a time variation of 0.5 to 3.5 s, obtaining the raw images. The acquired images were evaluated with the ImageJ software to determine the saturation time of the plates when exposed to X-ray beams and the qualitative resolution of each plate. The plates were found to saturate at different times when exposed under the same conditions to X-ray beams. By means of the images acquired with the breast phantom, it was possible to observe only structures of calcium carbonate with sizes greater than 177 μm.